Exclusion of plant input affects the temperature sensitivity of soil organic carbon decomposition. (September 2022) - Zhang, Xiuwei; Zhu, Biao; Yu, Fei-Hai; Wang, Peng; Cheng, Weixin
Highlights: In the early stage of incubation, plant input exclusion increased (Alfisol) or had minor effect (Mollisol) on Q10 . In the later stage of incubation, plant input exclusion decreased Q10 of both experimental soils. Decreases in substrate quality and availability predicted increases and decreases in Q10, respectively. Abstract: Plant residue input plays a vital role in cropland carbon (C) balance, which can be greatly affected by climate change. Our knowledge of the effect of plant residue on soil respiration is crucial for evaluating C exchange between the atmosphere and terrestrial ecosystems, but large uncertainties remain in the effect of plant input on the temperature sensitivity (Q10 ) of soil organic C (SOC) decomposition in cropland ecosystems. Here, soils were sampled from two bare fallow plots (including a Mollisol and an Alfisol with different climate and land-use history) and their adjacent old field plots, and were incubated at 10 °C and 20 °C for 815 days. The 'equal-time', 'equal-C', 'one-pool model' and 'two-pool model' methods were used to evaluate the Q10 of SOC decomposition. Results indicated that in the early stage of incubation, exclusion of plant input increased the Q10 (Alfisol) or had minor effect on the Q10 (Mollisol), which may be related to the interactions between substrate quality decrease (increase of chemical stability) and clay mineral suppression on microbial decomposition. However, in the later stage of incubation, plant residue removal decreased the Q10 values in both soils possibly due to the limitation of substrate availability on microbial decomposition. Overall, the role of plant input in the temperature sensitivity of SOC decomposition should be considered when predicting SOC stocks in a future warmer world.